High prevalence of Histoplasma capsulatum in bats and pigeons is linked to human histoplasmosis in an endemic area of Ecuador - Mora-Jaramillo, Naomi; Orlando, Solón Alberto; Rivera, Mireya; Echevarría, José; Carvajal, Elsy; Rodríguez-Pazmiño, Sebastián; Paredes, Darwin Santiago; Arcos Alcivar, Fabricio; Rebolledo, Valeria; Fuentes, Tais; Delgado, Odalys; Valencia, Pamela; et al. (Frontiers in Veterinary Science, 2025)
Histoplasmosis, a systemic mycosis caused by the fungal pathogen Histoplasma capsulatum, is a global public health concern, particularly in immunocompromised patients. The global burden of this disease is estimated in 500,000 people affected annually with around 100,000 cases progressing to disseminated histoplasmosis, the most severe clinical form of the disease with 30–50% mortality rate in treated patients. Histoplasmosis is very endemic in areas associated with river valleys. In South America, histoplasmosis is one of the most important causes of mortality in HIV patients, accounting for approximately 30% of deaths in this population, and it is frequently misdiagnosed. The animal reservoirs for these pathogens include bats and birds like pigeons, and fecal deposition in areas with high density of those animals represents hotspots of fungal contamination. In this work, we studied the prevalence of H. capsulatum in bats and pigeons from Guayas Province in Ecuador by PCR. A total number of 61 pigeons and 213 bats samples were collected, and the overall prevalence was 13.11% (95%CI: 10.54–15.68) and 21.14% (95%CI: 17.00–25.28), respectively. Moreover, Sanger sequencing analysis was carried out for hcp100 gene, followed by phylogenetic analysis including 17 sequences isolated from human patients in Guayaquil city (Guayas Province). Our results show that bats and pigeons are reservoirs for H. capsulatum linked to transmission to humans in Guayas Province. An integrative One Health surveillance and control program including animal reservoirs should be improved to reduce the burden of histoplasmosis, especially considering the high burden of HIV in Guayaquil city.